Perbaikan Kualitas Buah Anggur Bali (Vitis Vinifera L. Var. Alphonso Lavallee) melalui Aplikasi GA3 sebelum Bunga Mekar - ASTAWA, I NYOMAN GEDE; MAYADEWI, NI NYOMAN ARI; SUKEWIJAYA, I MADE; PRADNYAWATHI, NI LUH MADE; DWIYANI, RINDANG (Agrotrop : Journal on Agriculture Science, 2016)
Improvement of The Quality of Balinese Table grape (Vitis Vinifera L. Var. Alphonso Lavallee) using GA3 Application Before Flowering. Research concerning of “Improvement of Balinese Tablegrape (Vitis Vinifera L. Var. Alphonso Lavallee) using GA3 before flowering” had been done during May to August 2015 at the vineyard located at Kalianget Village, in Buleleng Regency, Bali. Theobjective of the research was to find out method in improving the quality of Balinese table grape using GA3 application. The experiment was designed as Randomized Block Designed, with GA3concentration as a treatment, i.e. 0, 50, 100, 150, 200 ppm. The results showed that, application of GA3 before flowering increased bunch length, improved oBrix, induced seedless, however decreasedberry weight.
Keywords: Balinese table grape; quality; GA3; before flowering